Promoting evidence-based practice: training health professionals for the evidence synthesis - Daniela Filipa Batista Cardoso; Diana Gabriela Simões Marques Santos; Joana Filipa Cunha Rodrigues; Nichole Bento; Rogério Manuel Clemente Rodrigues; Ana Filipa dos Reis Marques Cardoso
ABSTRACT Objective: To report the experience of the Portugal Centre For Evidence Based Practice (PCEBP): a JBI Centre of Excellence in the training of health professionals, researchers, and professors in the Comprehensive Systematic Review Training Program, a course on Evidence Synthesis, specifically on Systematic Literature Reviews. Method: This article aims to report the experience of the Portugal Centre For Evidence Based Practice: a JBI Centre of Excellence in the implementation of the Comprehensive Systematic Review Training Program that trains health professionals, researchers, and teachers to develop Systematic Reviews, according to the JBI approach. Results: By the end of 2020, 11 editions of the course had been developed with 136 participants from different educational and health institutions, from different countries. As a result of the training of these participants, 13 systematic reviews were published in JBI Evidence Synthesis and 10 reviews were published in other journals. Conclusion: The reported results and the students' satisfaction evaluation allow us to emphasize the relevance of the course for health professionals training on evidence synthesis.